Influence of Resistance Training Proximity-to-Failure on Skeletal Muscle Hypertrophy: A Systematic Review With Meta-Analysis - Refalo, MC; Helms, ER; Trexler, ET; Hamilton, DL; Fyfe, JJ (Springer Science and Business Media LLC, 2022)
Background and Objective: This systematic review with meta-analysis investigated the influence of resistance training proximity-to-failure on muscle hypertrophy. Methods: Literature searches in the PubMed, SCOPUS and SPORTDiscus databases identified a total of 15 studies that measured muscle hypertrophy (in healthy adults of any age and resistance training experience) and compared resistance training performed to: (A) momentary muscular failure versus non-failure; (B) set failure (defined as anything other than momentary muscular failure) versus non-failure; or (C) different velocity loss thresholds. Results: There was a trivial advantage for resistance training performed to set failure versus non-failure for muscle hypertrophy in studies applying any definition of set failure [effect size=0.19 (95% confidence interval 0.00, 0.37), p=0.045], with no moderating effect of volume load (p=0.884) or relative load (p=0.525). Given the variability in set failure definitions applied across studies, sub-group analyses were conducted and found no advantage for either resistance training performed to momentary muscular failure versus non-failure for muscle hypertrophy [effect size=0.12 (95% confidence interval −0.13, 0.37), p=0.343], or for resistance training performed to high (>25%) versus moderate (20–25%) velocity loss thresholds [effect size=0.08 (95% confidence interval −0.16, 0.32), p=0.529]. Conclusion: Overall, our main findings suggest that (i) there is no evidence to support that resistance training performed to momentary muscular failure is superior to non-failure resistance training for muscle hypertrophy and (ii) higher velocity loss thresholds, and theoretically closer proximities-to-failure do not always elicit greater muscle hypertrophy. As such, these results provide evidence for a potential non-linear relationship between proximity-to-failure and muscle hypertrophy.
Keywords: 4201 Allied Health and Rehabilitation Science; 42 Health Sciences; 4207 Sports Science and Exercise; Musculoskeletal; 0913 Mechanical Engineering; 1106 Human Movement and Sports Sciences; 1302 Curriculum and Pedagogy; Sport Sciences; 4201 Allied health and rehabilitation science; 4207 Sports science and exercise; Humans; Muscle, Skeletal; Resistance Training; Muscle Strength; Hypertrophy; Muscle, Skeletal; Humans; Hypertrophy; Muscle Strength; Resistance Training; Humans; Muscle, Skeletal; Resistance Training; Muscle Strength; Hypertrophy